Surface deployment of DAS systems: Coupling strategies and comparisons to geophone data. Issue 5 (30th August 2022) - Harmon, Nicholas; Rychert, Catherine A.; Davis, John; Brambilla, Gilberto; Buffet, William; Chichester, Ben; Dai, Yuhang; Bogiatzis, Petros; Snook, James; van Putten, Lieke; Masoudi, Ali
Abstract: Distributed acoustic sensing (DAS) systems are a recent technological development for seismic observations over a broad range of frequencies with a wide variety of applications. Typically, fibre‐optic cables are buried underground or cemented into well casings where the cables are well‐coupled to the ground. Quick and temporary surface deployment of cables has great potential utility in areas where rapid surveying and minimal disturbance of the subsurface are desired. However, proper mechanical coupling between the fibre and the ground is still a challenge for temporary surface deployments. Here we test four different coupling strategies for a DAS system deployed in a grassy field, including uncoupled, pinned under tension to the ground, weighted down by carpeting, and weighted down by a sandbag. We compare the DAS data to vertical component geophone data and estimated horizontal geophone data to assess the fidelity of DAS ground motion recordings. We find a completely uncoupled fibre is capable of recording seismic energy up to ∼10 m away from the source, while the pinned and weighted fibre record signals over several tens of metres. The DAS recordings compare favourably with the estimated horizontal displacement records from the multi‐channel seismic system. There is a good agreement between the phase of the signals acquired by the DAS system with that of the geophones, but there is a mismatch of up to a factor of two in the absolute amplitude at some frequencies. We perform several standard analysis techniques, including refraction and multi‐channel analysis of surface waves, on the coupled DAS data. Finally, the instrument response of the coupled DAS data to ground motions is determined using the estimated horizontal component from the multi‐channel seismic system. Surface deployments of DAS systems provide a complementary set of observations to standard vertical geophone deployments, for instance, if multi‐component geophones are not available. Also, there are some advantages in speed and ease of deployment of DAS in comparison to geophones depending on the coupling strategy used.